Reputation management through social networking platforms for PR purposes: A SEM-based study in the Jordan - Al Olaimat, Farhan; Habes, Mohammed; Al Hadeed, Ali Yahya; Al Jwaniat, Marcelle Issa (Frontiers in Communication, 2022)
Social networks are of greater importance for general and corporate purposes. Especially retailers today resort to these platforms to bridge a communication gap between their PR practitioners and consumers for reputation management purposes. This research also examines the Social network usage for Public Relations (PR), leading to Reputation Management in the Jordan ’s retail sector. The researchers developed the conceptual model at Theory of Reasoned Action and applied the Structural Equation Modelling (SEM). Results indicated by the Public Relations practitioners have a significant impact on controlling the customers' behaviour (p> 0.000). This Perceived Behavioral Control is an important factor in social network adoption for communication purposes (p> 0.048). Accompanied by instant communication ability (p> 0.000), these social networks and communication feasibility have a significant impact on Reputation Management (p> 0.035, p> 0.003). However, it is notable that, Attitude also mediated the Public Relations Practices concerning Perceived Behavioral Control (p> 0.060), indicating that the Theory of Reasoned Action significantly determined the factors determining the Social Networks usage and adoption for the reputation armament purposes. Thus, it is concluded that using social networks for Public Relations practices is the need of the day. Especially when using them for reputation management, companies consider different factors that further assist their digital networks adoption process, leading to fruitful outcomes. Further, the researchers have discussed the study contributions and made recommendations for future researchers.